Football camps as a new service business idea for Böda Sand Camping - Saukkonen, Marjaana; Pesu, Salli-Kaisa (2020)
The assignment for the thesis came from international project called VISIT. VISIT stands for Versatile Islands Cooperating for New Services and Innovation in Tourism. The goal of the project is to create new innovative services for small and medium enterprises in the tourism field on European islands. The main goal of the thesis was to create a business plan for a new service idea developed as a solution to the camping company called Böda Sand, on how to prolong the high season. The new service idea was born during intensive study program on Öland where the authors took part in May 2019. The second purpose of the work was to pilot video material in the thesis, as it is the first time hospitality management students include video material into thesis. Knowledge base and theory used in the thesis is about business plan, business idea, business model canvas, service logic business model canvas and digitalization. Authors used a questionnaire as a quantitative research method and interviews as a qualitative method to collect data to create a business plan. The goal was achieved by authors first familiarizing themselves with the theory of the subject and then gathering information from the company and potential customers. The outcome of the thesis is a new service idea described by service logic business model canvas. Results of the empirical research indicate that the idea of organizing football camps in Böda Sand is realistic. The location of Böda Sand is not very convenient for football clubs from Finland or northern Sweden, but football clubs from southern Sweden and possibly clubs from Denmark could find the possibility of organizing camps in Böda Sand as a liable option. Böda Sand Camping has all the necessary facilities for organizing football camps which could lead to a new customer segment and solve the problem of the short high season. To start with a new service idea in action, the authors propose Böda Sand to contact the local football club and discuss about possible cooperation. As Böda Sand does not have a proper football field in the camping site, cooperation with the closest football club would be necessary. Another suggestion is to translate the website to English as at the moment it is only in Swedish. This limit the customers only to Swedish football clubs and international clubs cannot find the option for arranging the camps. The business idea of the thesis can be modified for different sports and age groups. For example, a kayak camp for seniors or swim camp for children are possible. 6-0! is a football project which is funded by Erasmus+ and it is a good benchmark for football camp service business idea. The idea of the project is to get seniors moving through football and it can be implemented for elderly who would not need a bigger football field. The data of the thesis can be beneficial for different concepts.